What is man that God is mindful to him: An Exegesis of Psalm 8 - Siby, Robert; Kaparang, Grace Fresania (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Even when human may choose to believe or not to believe in God, Psalm 8 bears witness the value of human being in God’s eyes despite of the fall, sin and rebellion. The purpose of this paper is to go through the exegetical analysis as to seek appropriate understanding and application of Psalm 8 to the wondrous relationship of the Almighty God and frail human beings through historic-grammatical method of finding meaning, observing literary genre and context, structural analysis, and then looking for its spiritual and theological application. The conclusion of the study is that Psalm 8 is a hymn of praise and through meditation on the Name and glory of God reflected in His creation, Psalter asks the reader of the book of Psalm to experience the joyful praise and adoration to the creator of His mighty work of creation and of His attention to human beings.  The grandeur of the heavens, the artistry of God, and the dignity of human beings tell the reader about the mighty God who deserve our praise and worship. Psalter let the earliest speech of a child can be heard in the grandeur of heavens (8:1c and 8:3a) and shows the frailty, weakness, and limitation of man (8:4a) in the middle of the fingers (8:3a) and the hands of God (8:6a).  Both arrangements demonstrate that Human as created beings are not left without attention but are heard and cared of by God.  Human beings are created to praise God, the creator, as their nature. Realizing human’s frailty and nothingness, while powerful God is mindful of them in spite of the unbelieving and sin manifested to Him, human may truly praise the Lord with the Psalmist: “What is man, that thou art mindful of him? and the son of man, that thou visit him?” “O LORD our Lord, how excellent is thy name in all the earth!” (Ps 8:4,1,9). The greater glory and holiness are given back to God, human dominion over creation once is taken, but through Jesus it was redeemed, and give hope to humanity further Glory in Him alone.